Pancreatic Adaptive Responses in Alcohol Abuse: Role of the Unfolded Protein Response - Lugea, Aurelia (Pancreatology, 2015)
Although alcohol abuse is associated with a spectrum of pancreatic diseases from acute self-limiting episodes of pancreatitis to recurrent acute pancreatitis, chronic pancreatitis and pancreatic cancer, the majority of those who drink excessive amounts of alcohol do not develop pancreatic disease. One overarching hypothesis is that alcohol abuse requires additional risk factors, either environmental or genetic, for disease to occur. However, another reason why alcohol abuse leads to pancreatic disease in so few individuals could also be a result of alcohol-induced activation of adaptive systems that protect the pancreas from the toxic effects of alcohol. We have turned to investigating the potential role of the unfolded protein response (UPR) of the endoplasmic reticulum (ER) to identify potential pathways that can lead to protection of the pancreas from pancreatic diseases with alcohol abuse. We discuss the pathways involved in protection as well as those involved in development of pancreatic pathology. The remarkable ability of the pancreas to adapt its machinery to alcohol abuse using UPR systems and continue functioning is the likely reason that pancreatitis from alcohol abuse does not occur in the majority of heavy drinkers. These findings additionally indicate that methods to enhance the protective responses of the UPR can provide opportunities for treatment of pancreatic diseases.